Measuring the Effectiveness of XL Axiata's Twitter Account in Handling Customers Complaints - Siregar, Adrian Irshadi; Iskandar, Budi Permadi (Journal of Business and Management, 2012)
Conventionally, customer service is an office branch where customers can get solutions regarding the provider’ troubled services. XL Axiata established such customer service, named XL Center, in three places, namely in Jalan Martadinata, Cimahi, and Buah Batu. The company also operates customer services in two malls, in Dukomsel and in Bandung Electronic Center (BEC). The customers, however, have to spend efforts, costs and time to get services there. In addition to conventional customer service, XL Axiata utilizes a new social media tool to provide such services. The firm became the first telco that realize the importance of new media in servicing its users. In February 2012, it opened a Twitter account which specialized for customer service, named @XLCare. Unlike other telcos that treat its Twitter account only as a promotional tool, XL Axiata account is functioned as customer service. Besides @XLCare, XL Axiata has @XL123 as its promotional instrument. Both accounts allow the firm to have two ways interaction to its customers. Therefore, customers can access solutions through its personal gadgets, such as laptops, tablet PCs or smartphones. Purpose: The study objective is measuring the effectiveness of @XLCare in Serving Complaining Customers. The Twitter account effectiveness has been measured with three identifications, namely: a. Reverberation of Customers’ Voices. b. Satisfaction of Complaining Customers. c. Brand Switching Activities.Design/methodology/approach: The methodology of research included research framework and sampling method. The research framework is Complaints-XL Axiata Customer Care Responses-Satisfactory Level-Brand Switching with detailed method of collecting complaint information, respondent’s interview and interview result. The sampling method use Topsy.com as the tools to decide the population and Slovin Theory as the tools to decide the sample.Findings: There are six parts of data presented in the research. First part presents about the topics of respondent complaint with XL signal problem as the most reason (38 %). Second part presents about the types of @XLCare responses with direct message as the most type of response (73 %). Third part presents about the final thoughts of respondent about @XLCare with most thought is satisfied (26 %). Fourth part presents about the brand switching activity of respondents with most respondents not switched (79. %). Fifth part presents about the reasons of not-switched respondents with keeping number as identity as the most reason (24 %). Sixth part presents about the reasons of switched respondents with bad signal quality as the most reason (57 %).In general, @XLCare effectively response the complaining customers based on three aspects. First, the reverberation of customer voice with most complaining customers shared the experience with @XLCare (63 %). Second, the complaining customer’s satisfaction with most of final response is promoting the brand of @XLCare or XL Axiata (26 %). Third, the brand switching activity that most of complaining customers not switched to another brand (79 %). The recommendation included four aspects of technical issues recommendation, non-technical issues recommendation, service recovery development recommendation, and further study recommendation.Key Words: Marketing, Twitter, Social Media, Augmented Product, Customer Service, After Sale Service, XL Axiata.Category: Marketing.